Evaluation of local oxygen consumption in human flexor digitorum suoerficialis muscle by near infrared spectroscopy - Erdoğan, Sinem Burcu. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2007., 2007)
A strong relationship between mechanical and physiological conditions of skele- tal muscle determines the force generated by that muscle. The aim of this study was to evaluate the relationship between local oxygen consumption and local force produced during isometric contractions at varying biomechanical conditions. Another aim of the study was to investigate the e ect of relative position and absolute length changes on local energy consumption of exor digitorum super cialis (FDS) muscle during isomet- ric contractions performed at various muscle length and force levels. Nine healthy male subjects performed sustained isometric handgrip exercise by continuously pressing on a hand dynamometer. The handgrip exercise was performed while the wrist is (i) maximally exed, (ii) maximally extended and (iii) in neutral position. Local oxygen consumption (mVO2) and time course of recovery (trec) of FDS muscle were measured by functional near infrared spectroscopy (fNIRS). mVO2 and trec were linearly related with force level up to 40% of maximal voluntary contraction force (MVC) at all wrist positions (p<0.05). At each force level, mVO2 was observed to be lowest when the wrist was maximally extended (p=0.0004). Both parameters presented a decrease as the wrist was extended. The results imply that local energy consumption has a dependence on muscle relative position and length. It is suggested that myotendinious force transmission between a muscle and its surrounding structures might be a determinant of local of energy consumption.|Keywords: Near infrared spectroscopy, local oxygen consumption, isometric handgrip exercise.
Keywords: Near infrared spectroscopy.; Oxygen consumption (Physiology); Isometric exercise -- Physiological effect.